EFFECT OF DADIM SWARASA (POMEGRANATE JUICE) ON PANDU IN FEMALES W.S.R.TO. IRON DEFICIENCY ANAEMIA - Ghawte Sanket Annasaheb; Shinde Bhagwat; Pande P. P.; Deshpande P.R. (International Journal of Applied Ayurved Research, 2016)
Background: Anaemia refers to state in which level of Hemoglobin in blood below the reference range appropriate for age and sex. Around 30% of total world population is anaemic and half of these some 600 million people have iron deficiency. In Ayurveda , Pandu (Anaemia) mentioned in Charaka Samhita, Yogaratnakara, Vagbhata in which skin, nails, eyes become fade called Pandu. It can be correlated with Anaemia. The clinical features of anaemia reflects diminished oxygen supply to the tissues, skin become pale. Menorrhagia is a common cause of anaemia in female. Dadim Swaras (Punica granatum) is selected for their wide spectrum action on Anaemia like Hrdya(Good for Heart) Tridoshnashak , good source of Folate, Vitamin K, Vitamin C . Aim: To evaluate the effect of Dadim Swaras in the treatment of iron deficiency anaemia . Materials and Methods: Total 20 female patients of iron deficiency anaemia with 4weeks duration were enrolled and randomly allocated to GroupA (Oral Dadim swaras 50ml daily once at morning) , Group B (Only Tablet Ferrous sulfate 100mg Daily Once) . Duration of treatment was considered about 1 month. Plasma ferritin, Hemoglobin, Hridspandana(Palpitation), Shwasa (Breathlessness),Panduta (Paleness) observed at weekly interval. Results: With the treatment of 4 weeks, Group A showed dramatic improvements in signs and symptoms. Resolution of Plasma Ferritin , Hemoglobin, Hridspandana(Palpitation), occurred in about 100% of patients. Whereas 90% of patients having reduction in Panduta (Paleness) and cessation of Shwasa (Breathlessness) in 70%. In patients of Group B, Panduta and Mean corpuscular volume shows good results in only 60%. Cessation of Hridspandana and Shwasa occurred in 50% whereas Hemoglobin elevetated in 70%. So use of Dadim Swaras (Pomegranate Juice) showed significant effect when compared before and after treatment by applying ‘t’ test to parameters, p<0.10. Conclusion: Dadim Swaras (Pomegranate Juice) used in Iron deficiency anaemia were found more effective than Ferrous sulfate.